"Sex" and "Gender": Two Confused and Confusing Concepts in the "Women in Corporate Management" Literature - Borna, Shaheen (Journal of business ethics, 2003)
In this article we attempt to reduce the confusion surrounding the concepts of "sex" and "gender" in the literature of "Women in Corporate Management." We contend that the incorrect usage of these concepts not only creates confusion in the literature, but also casts a shadow over the research findings in this area. We offer specific recommendations for authors as means to reduce the confusion in future research.